2023
DOI: 10.1002/mds.29358
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal alpha‐Synuclein Pathology and Enteric Gliosis in Advanced Parkinson's Disease

Abstract: plete blood cell count-derived ratios can be useful biomarkers for neurological diseases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…In previous studies, the conformation-specific 5G4 antibody yielded promising results in intestinal tissue. Indeed, this antibody has been used successfully to detect aSyn deposits in the colon and duodenal mucosa, yielding a sensitivity 83.3% and a specificity 88.2% in the colon, as well as a sensitivity of 100% and a specificity of 83.3% in the duodenum (15,16). In contrast to these data, we were unable to distinct between PD patients and controls on the basis of 5G4 or MJFR-14 immunoreactivity in rectal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the conformation-specific 5G4 antibody yielded promising results in intestinal tissue. Indeed, this antibody has been used successfully to detect aSyn deposits in the colon and duodenal mucosa, yielding a sensitivity 83.3% and a specificity 88.2% in the colon, as well as a sensitivity of 100% and a specificity of 83.3% in the duodenum (15,16). In contrast to these data, we were unable to distinct between PD patients and controls on the basis of 5G4 or MJFR-14 immunoreactivity in rectal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological issues have posed great challenges, including the insufficient sensitivity and specificity of some α-synuclein immunohistochemical approaches for distinguishing PD patients from controls [ 21 ]. Still, there are studies that show promising results, such as a recent report of duodenal biopsies examined using the conformation-specific 5G4 α-synuclein antibody that preferentially detects aggregates [ 100 ]. This study found greater α-synuclein aggregation in PD cases compared with controls and detected pathology in both early- and late-stage PD patient biopsies [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, there are studies that show promising results, such as a recent report of duodenal biopsies examined using the conformation-specific 5G4 α-synuclein antibody that preferentially detects aggregates [ 100 ]. This study found greater α-synuclein aggregation in PD cases compared with controls and detected pathology in both early- and late-stage PD patient biopsies [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the gut, ER stress mainly involves cells with high secretory phenotype, including PCs and GCs, leading to dysfunctional defense barrier, altered intestinal permeability and unbalanced composition of the gut microbiota 149 . In contrast, studies suggest that aggregation of neurodegenerative proteins occurs in the gut at different stages of neurodegenerative diseases, 150,151 as well as in sporadic cases of IBD 152 . Protein aggregates are involved in several pathological events including degeneration of nerve fibers in the enteric nervous system (ENS) and activation of inflammatory response with expression of inflammatory cytokines 153,154 .…”
Section: The Role Of Er Stress Along the Gut–brain Axismentioning
confidence: 99%